Humanized monoacylglycerol acyltransferase 2 mice on a high-fat diet exhibit impaired liver detoxification during metabolic dysfunction-associated steatotic liver disease - Corbalan, J. Jose; Jagadeesan, Pranavi; Nickels , Jr, Joseph T. (PLOS ONE, 2025)
Obesity significantly increases the risk of hyperlipidemia, type 2 diabetes, and liver disease. This study examined humanized monoacylglycerol acyltransferase 2 mice (HuMgat2) and their response to a high fat diet (HFD) while investigating hepatocyte dysfunction during obesity development. HuMgat2 mice fed a HFD exhibited hyperlipidemia, hyperglycemia, insulin resistance, and metabolic dysfunction-associated steatotic liver disease (MASLD). Elevated levels of cholesterol and triglycerides were associated with increased expression of lipogenic genes and accumulation of nuclear Srebp1/Srebp2. Mice fed a HFD demonstrated impaired insulin signaling and increased glucose production through the expression of gluconeogenesis genes. Liver fibrosis was characterized by collagen deposition and activation of Jak2-Stat3 signaling, resulting in hepatocyte apoptosis. RNA sequencing identified extracellular matrix degradation and apolipoprotein metabolism as being altered. Levels of cytochrome P450 enzymes were downregulated, as indicated by decreased Cyp2b10 and Cyb3a11 levels, alongside reduced expression of the di- and tri-carboxylic acid transporter Slc13a2, correlating with elevated Krebs cycle intermediates. Notably, HuMgat2 mice exhibited responses to a high-fat diet that were comparable to those observed in mMgat2 mice. These findings suggest that HFD consumption and concomitant obesity disrupts metabolite homeostasis, contributing to liver damage and cell death. They also further validate HuMgat2 mice as an excellent preclinical model for testing human MOGAT2 inhibitors as therapeutics for treating obesity.